RELASI POLITIK HUKUM, NILAI MORAL, DAN KEPASTIAN HUKUM DALAM PERSPEKTIF ASAS KEADILAN DI INDONESIA - Rahmanto, Faiz (Jurnal Ilmiah Advokasi, 2025)
The phenomenon of political dynasties in Indonesia has generated tension between formal legal certainty and public moral values, particularly following Constitutional Court Decision No. 90/PUU-XXI/2023, which set a constitutional precedent regarding the age requirement for presidential and vice-presidential candidates. This study aims to analyze this dilemma from the perspective of substantive justice. The method used is normative legal research with a statutory and literature-based approach. The findings show that although dynastic politics does not formally violate positive legal norms, such practices have the potential to undermine the principles of justice, equality, and democratic integrity. Therefore, it is essential to formulate a legal approach that balances normative certainty with moral legitimacy within the framework of a democratic rule of law. Keywords: Legal Politics; Moral Values; Legal Certainty; Justice